Enhancing current density of perovskite solar cells using TiO2-ZrO2 composite scaffold layer. (December 2016) - Che, M.; Zhu, L.; Zhao, Y.L.; Yao, D.S.; Gu, X.Q.; Song, J.; Qiang, Y.H.
Abstract: A novel scaffold layer composed of TiO2 -ZrO2 composite was fabricated for perovskite solar cell. Compared with pure TiO2 nanoparticles (NPs), the relatively larger ZrO2 NPs could increase film roughness and enhance light-scattering effect in TiO2 -ZrO2 composite films. The device exhibited outstanding power conversion efficiency (PCE) of 11.41%. The morphology and aggregation of particles, three-dimensional roughness, as well as the ingredient and micro-structure of FTO/compact TiO2 /TiO2 -ZrO2 was investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscope (AFM), energy dispersive spectrometer (EDS), and X-ray diffraction (XRD), respectively. Moreover, the optical property of TiO2 -ZrO2 films for visible light was characterized by UV–visible absorption spectroscopy (UV–vis), and its influence on quantum yield of the device was further demonstrated by incident photon-to-electron conversion efficiency (IPCE). Owing to the inert oxide, the short-circuit current density of perovskite solar cell using TiO2 -ZrO2 composition as scaffold layer increased by 21% compared to the one employing pure TiO2 mesoporous film.